1999
DOI: 10.1262/jrd.45.273
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Profiles of Growth Hormone, Prolactin and Insulin-like Growth Factor-I during Gestation, Lactation and the Neonatal Period in Goats.

Abstract: Abstract. The objectives of this research were to characterize plasma profiles of growth hormone (GH), prolactin (PRL) and insulin-like growth factor-I (IGF-I) during gestation and the lactation period in goats, as well as in their suckling growing kids. There were no obvious changes in the GH or PRL profiles during gestation, but secretion of both GH and PRL increased acutely after parturition. The elevated GH concentrations were maintained until 3 months after parturition, whereas the PRL concentrations decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Plasma LH, FSH and GH concentrations were measured by a double-antibody RIA procedure with slight modifications [24,25].…”
Section: Radioimmunoassay (Ria)mentioning
confidence: 99%
“…Plasma LH, FSH and GH concentrations were measured by a double-antibody RIA procedure with slight modifications [24,25].…”
Section: Radioimmunoassay (Ria)mentioning
confidence: 99%
“…Hashizume et al [4] suggested that as the stages of pregnancy are considered anabolic for the dam with i n c r e a s e d p r o t e i n a n d f a t d e p o s i t i o n , h i g h concentrations of IGF-I may play an important role in supporting metabolism during pregnancy in animals and stimulate fetal growth by activating the placental transport of nutrients to the fetus. The ir-IGF-I level in the present work showed a similar pattern to the results of Hess-Dudan et al [5].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IGF-I concentrations were measured by a double-antibody RIA procedure [10] as described in a previous paper [4]. Levels of immunoreactive (ir-) inhibin, follicle stimulating hormone (FSH), luteinizing hormone (LH), equine chorionic gonadotrophin (eCG), estradiol-17β (E 2 ) and progesterone (P 4 ) in peripheral blood were measured by RIA as described in previous papers [2,4].…”
Section: Radioimmunoassaymentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role and source after luteinization and/or ovulation of these follicles is still to be investigated. It was suggested that maternal IGF-I stimulated by activating the placental transport of nutrients [7], and the IGF-I was shown to be adjunctively and directly associated with fetal growth in human [20]. However, it was reported that there was a loss of the relationship between fetal weight and maternal plasma IGF-I concentrations in sheep [8].…”
Section: Discussionmentioning
confidence: 99%